Brief Morita Therapy for Social Anxiety: A Single Case Study of Therpeutic Changes - Ishiyama, Ishu (Canadian Journal of Counselling and Psychotherapy, 2011)
Morita therapy is a Japanese therapy for anxiety-related problems developed by Shoma Morita (1874-1938) in the 1910's. Through didactic discussion and confrontation, it modifies anxious clients' self-critical thinking and unproductive self-preoccupation. Clients in Morita therapy are encouraged to appreciate the existential and self-actualizing meaning of anxiety and to translate it into constructive action instead of resisting and becoming preoccupied with anxiety symptoms in a self-defeating manner. Using a multiple baseline design across two target problems (fear of speaking in groups and fear of approaching strangers), the present study examined therapeutic changes associated with brief (3-session) Morita intervention in a socially anxious client. Notable changes regarding both problems were observed immediately after intervention and in the follow-up phase in the client's ratings on (1) acceptance of anxiety, (2) problem severity, and (3) effectiveness in coping with anxiety problems. Qualitative information provided by the client suggested the lasting therapeutic impact of Morita-based interpretation of anxiety and confrontation. Suggestions are given for future single-case experimental research on Morita therapy.